Sequential optimization of essential nutrients addition in simulated dairy effluent for improved Scenedesmus sp ASK22 growth, lipid production and nutrients removal - Pandey A.; Srivastava S.; Kumar S. (My University, 2025)
Combined process development for efficient recycling of nutrients using microalgae may deliver realistic answer to both environment management and energy generation. This study demonstrates the biomass and lipid yields of Scenedesmus sp. ASK22 and simultaneous nutrient remediation of simulated dairy effluent (SDE). The Plackett-Burman method is employed to screen essential nutrients that effect the Scenedesmus sp. ASK22 lipid production grown in SDE. Central composite design (CCD) is employed to evaluate the interactive effect and optimization of variable. The significant variables are observed to be NaNO3, EDTA, micronutrients and initial pH and these variables are screened on the basis of high confidence levels (p < 0.05). The optimum value of initial pH, NaNO3 (g L−1), EDTA (mg L−1) and micronutrients (ml L−1) were found to be 7.18, 1.21, 0.848 and 0.969, respectively for maximum lipid accumulation. Biomass yield and nutrients sequestration rate is also improved by addition of nutrients at optimum level. The maximum biomass and lipid yield of Scenedesmus sp. ASK22 in the optimized medium were 2.68 g L−1 and 1.05 g L−1, respectively resulting in an overall 2.19 and 2.8-fold increase compared to without nutrient added SDE. The chemical oxygen demand (COD), nitrate and phosphate removal efficiency were also increased by 10.68%, 17.59% and 19.36%, respectively in optimized SDE. The C16:0, C18:0, C18:1 and C18:3 were the dominant fatty acids in lipid which indicates a great potential of Scenedesmus sp. ASK22 biodiesel production and simultaneous nutrients sequestration process using nutrients added SDE. © 2019 Elsevier Ltd